The use of multimedia interactive to improve students science literacy in the new normal era - Ainus Shofawati; Wahono Widodo; Dhita Ayu Permata Sari (Jurnal Pijar Mipa, 2023)
This study aims to describe the influence of interactive multimedia on students' science literacy in the new normal era and student responses after learning using interactive multimedia on energy flow materials. The type of research used is pre-experimental design research through one group pretest-postest design. The subjects in this study were 31 students of class VIIC in Muhammadiyah Junior High School 2 Taman Sidoarjo, even semester of the 2021/2022 academic year. Data collected by techniques use observation, tests, and questionnaires. Research instruments include observation sheets for the implementation of learning, science literacy tests, and student response questionnaire sheets. The data were analyzed descriptively using the N-Gain test, the implementation observation sheet, and the response questionnaire. The results showed that the implementation of learning using interactive multimedia on energy flow materials got the criteria for being carried out properly. Students' science literacy skills increased from an average pretest score of 38.5 to 81 on the posttest, with an average N-Gain score of 0.69, categorized as moderate. The learning process and the use of interactive multimedia applications on energy flow materials were also responded to positively by students. Based on the description above, learning using interactive multimedia on energy flow materials can improve students' science literacy skills in the new normal era.